Clinical characteristics of cerebral venous thrombosis in patients with systemic lupus erythematosus - LIAO Qiu-ju; YANG Xiao-yi; ZHAO Yi; SU Li (Chinese Journal of Contemporary Neurology and Neurosurgery)
Objective To analyze the clinical manifestations, imaging features, treatment and prognosis of patients with systemic lupus erythematosus (SLE) combined with cerebral venous thrombosis (CVT). Methods and Results Clinical data of 19 patients with SLE combined with CVT (SLE combined with CVT group) and 38 age and sex matched patients with SLE without CVT (SLE without CVT group) hospitalized in Xuanwu Hospital, Capital Medical University from January 2013 to December 2024 were retrospectively analyzed. SLE combined with CVT group had higher D-dimer (P = 0.001), lupus anticoagulant (P = 0.001), and Systemic Lupus Erythematosus Disease Activity Index-2000 (SLEDAI-2000) at admission (P = 0.000) compared with SLE without CVT group. In SLE combined with CVT group, headache (18/19) was the most common neurological symptom. Cerebrospinal fluid (CSF) pressure increased in 14 cases (14/16). The most common cases of thrombosis were transversal sinus (17/19) and sigmoid sinus (17/19). Seventeen cases (17/19) had ≥ 2 venous sinuses involved. Twelve cases had other sites venous thrombosis occurred simultaneously. All patients of SLE combined with CVT group were treated with glucocorticoids, immunosuppressants and anticoagulation therapy. The average follow-up period was (77.14 ± 33.46) months. During the follow-up, 16 cases improved, one case died of concurrent infection, and 2 cases were lost to follow-up. Conclusions CVT is a rare and severity complication of SLE. Headache is the most common neurological symptom, and transversal sinus and sigmoid sinus are the most common sites of thrombosis. For patients of SLE combined with CVT, treatments such as glucocorticoids and immunosuppressants need to be strengthened after venous sinus mechanical thrombectomy. Early recognition and active treatment can obtain good curative effect.